2014
DOI: 10.1016/j.cimid.2014.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Tularaemia: A challenging zoonosis

Abstract: a b s t r a c tIn recent years, several emerging zoonotic vector-borne infections with potential impact on human health have been identified in Europe, including tularaemia, caused by Francisella tularensis. This remarkable pathogen, one of the most virulent microorganisms currently known, has been detected in increasingly new settings and in a wide range of wild species, including lagomorphs, rodents, carnivores, fish and invertebrate arthropods. Also, a renewed concern has arisen with regard to F. tularensis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
109
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(115 citation statements)
references
References 92 publications
(232 reference statements)
2
109
0
1
Order By: Relevance
“…During this study, the cases observed of the most common disease in the investigated schools between teachers and students varied between acute disease (sore throat, stomach ache, cold, fever, tonsillitis, flu cough, headache and dizziness) and chronic disease (asthma, anaemia, urinary tract infection, rheumatoid, eczema, chest allergy) ( Table 2). It was observed that the diseases were common when the student›s age was between (11-16) years but, the diseases were fewer when the teacher›s age was between (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Results of this study confirm the considerable microbial contamination of most investigated school settings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During this study, the cases observed of the most common disease in the investigated schools between teachers and students varied between acute disease (sore throat, stomach ache, cold, fever, tonsillitis, flu cough, headache and dizziness) and chronic disease (asthma, anaemia, urinary tract infection, rheumatoid, eczema, chest allergy) ( Table 2). It was observed that the diseases were common when the student›s age was between (11-16) years but, the diseases were fewer when the teacher›s age was between (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Results of this study confirm the considerable microbial contamination of most investigated school settings.…”
Section: Resultsmentioning
confidence: 99%
“…During lessons and after lessons the number of microorganisms was much lower. But, Carvalho CL et al [35] evaluating many shopping centres in Hong Kong found different bacteria levels on the weekend when the number of people inside the building increased. However, Stryjakowska-Sekulska et al [9] reported in their investigation just after the short period of high microorganism's concentration in the air of investigated rooms a gradual decrease of microbial contamination.…”
Section: Resultsmentioning
confidence: 99%
“…F. tularensis have the ability to intensively multiply within macrophages. The virulent ability of the germ interferes with the resistance of the host organism, resulting in bacterial cell division in the cytoplasm (Carvalho et al 2014). It can trigger off a cell death by apoptosis, releasing the bacteria to infect new cells (Glinski and Kostro 2003).…”
Section: Pathogenesismentioning
confidence: 99%
“…It is widespread throughout the Old World and North America [79]. On the Eurasian continent, tularemia is traditionally reported from Scandinavian countries, particularly from Sweden [80,81]; from countries of Central Europe, including Germany [82,83], Austria [84,85], the Czech Republic and Slovakia [84,86]; from countries of the former Soviet Union [87][88][89]; from Central Asia [90][91][92], including Mongolia [93]; and from the Japanese islands [94,95].…”
Section: Epidemiologymentioning
confidence: 99%